Differences in conditional self-discrimination between wistar and Sprague-Dawley strains (2011)
Conditional self-discrimination capacity was studied and compared between two strains of 4 weeks old Rattus norvegicus. Each strain (15 Wistar and 16 Sprague-Dawley) was considered as a group, both trained under an escape paradigm in which a lever was associated to presence or absence of methylphenidate. The dependent variable was measured during the phase of extinction. Significant differences were found for self-discrimination capacity, and between groups, being the Sprague-Dawley the strain with a better performance. Even though both strains are able to discriminate their internal state, and learn to use such state as a discriminative stimulus, the social variable seem to be a remarkable component of the differences found in the strains performances.